Verseny a műholdas piacon - zsúfoltság, viták és szűkülő erőforrások (Competition in the Satellite Market: Congestion, Contention and Shrinking Resources) - Diána Daczi; Péter Vári; Balázs Bartóki-Gönczy (KözigazgatásTudomány)
The rise of the mega-constellations has set a new precedent in orbital congestion, simply as a result of the increased number of satellites. According to the United Nations Office for Outer Space Affairs, since the launch of Sputnik-1, 17,263 objects has been launched to space, of which 11,330 satellites are orbiting the Earth in June 2023, that means 37.94% increase since January 2022. We are used to the novelties of space communication, until now had a steady development, but now its pace changed: until 2020 only 10,308 were launched, but in the last 3 years 6,995 objects, which means 40.29% of all objects in this period. Most of these objects are communication satellites, which are deployed in increasingly connected systems in low Earth orbit (LEO). While the problems of space debris continue and the lack of space traffic regulation, i.e. the question of sustainability, have been at the centre of scientific and professional debates for years, we hear little about radio frequency interference, while this problem also threatens the sustainable development of human space activities. Constellations placed in LEO orbit – similarly to the characteristics of the better-known geostationary satellite constellations – have wide coverage and an enormous amount of satellites. While the appearance of these constellations brought revolutionary changes in the development of the global space industry, the global market of satellite telecommunications cannot be managed within the framework of the current international commercial cooperation defined in the early 1990s.